Network and Relations of Islamic Libraries in the Era of the Islamic State: Medieval Islamic Libraries - Setiawan, Setiawan; Ansor, Sokhibul (Universitas Wijaya Kusuma Surabaya, 2024)
Purpose Research. The development of libraries during the Islamic Daulah era grew rapidly, and this was inseparable from the role of the leaders of the state who had noble ideals by collecting research results from various philosophers. After the research was collected, they put the results or writings in the library. Therefore, this research aims to determine the role of libraries during the Islamic Daulah era because many works and activities were produced during this medieval era, and libraries developed as a center for study for scientists. Method. This research uses a qualitative descriptive research method, which means that it uses the Naturalistic Inquiry method. Data Analysis. The data analysis method used is literature review. The method research action by examining sources related to the theme of this research until the concrete data will be found. Results and Discussions. Research result, 1) During the Umayyah period, it made a breakthrough by developing private libraries, but also developing public libraries, 2) in the Abasiyyah dynasty there were technical activities regarding libraries starting from procurement, processing library materials. 3) The existence of a conflict between the Umayyah dynasty and the Abbasid dynasty was not a problem for these two dynasties. Keywords: Library, library collaboration, Daulah Islam